IMPLEMENTASI MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUAL (SAVI) BERBANTUAN MEDIA AUDIOVISUAL DALAM PEMBELAJARAN KETERAMPILAN MEMBACA PUISI KELAS X SMAN 1 V KOTO TIMUR - Diana Putri Wulandari; Dewi Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Poetry recitation requires an instructional model that actively engages students and provides meaningful learning experiences. One instructional model that can be applied is the Somatic, Auditory, Visual, Intellectual (SAVI) learning model supported by audiovisual media. This study aimed to describe the implementation of the SAVI learning model assisted by audiovisual media in teaching poetry recitation to tenth-grade students at SMAN 1 V Koto Timur. This study was part of a quantitative experimental study employing a Pretest–Posttest Control Group Design. However, this article specifically focuses on describing the implementation of the SAVI learning model in the experimental class. The research data were obtained through a poetry recitation performance test and documentation. The findings revealed that the implementation of the SAVI learning model assisted by audiovisual media was carried out in accordance with its instructional stages, namely somatic, auditory, visual, and intellectual. The learning process began with the presentation of a poetry recitation video as a learning stimulus, followed by observation, discussion of poetry recitation techniques, poem analysis, and individual poetry recitation performances in front of the class. The implementation resulted in a systematic, interactive, and student-centered learning process. Therefore, the SAVI learning model assisted by audiovisual media can be considered an alternative instructional approach for teaching poetry recitation at the senior high school level.